Effect of dissolution pathways of polyacrylonitrile on the solution homogeneity: Thermodynamic- or kinetic-controlled dissolution. (28th September 2020) - Eom, Youngho; Ju, Hyejin; Park, Yeonju; Chae, Dong Wook; Jung, Young Mee; Kim, Byoung Chul; Chae, Han Gi
Abstract: Dissolution behavior of polyacrylontrile (PAN) in N, N -dimethylformamide (DMF) and dimethylsulfoxide (DMSO) is investigated in terms of dipole-dipole interactions at polymer-solvent interface. Fourier-transformed infrared (FTIR) imaging of polymer-solvent interface under static dissolution condition at 25 °C and 60 °C exhibits the gel-like swollen layer in the early stage of dissolution for both solvents. This layer readily disappears in PAN-DMSO and DMSO molecules penetrate deep into the polymer phase, whereas that in PAN-DMF is still observed until 12 h even at 60 °C. The better dissolving ability of DMSO is interpreted by higher intrinsic viscosity and lower Huggins' constant. The solubility (solution homogeneity) is also evaluated by rheological analysis in a wide concentration range of 8–20 wt%. At above 15 wt%, DMSO produces homogeneous solution at 60 °C even without stirring, showing the lower Newtonian flow region. On the other hand, it is necessary to apply vigorous stirring and heating for PAN-DMF system in order to prepare concentrated solution. DMSO provides greater slope of the Cole-Cole plot by rheological measurement than DMF, indicating better solution homogeneity in PAN-DMSO. The FTIR spectra and 2D correlation analysis show that both DMSO and DMF dissolve PAN in a way of sequential contributions of enthalpic and entropic factors. However, DMSO exhibits predominant contribution by enthalpic factor, suggesting that enthalpy change of mixing is a driving force of PAN dissolution in DMSO, whereas dissolution of PAN-DMF is governed by kinetic control. Graphical abstract: Image 1 Highlights: Solution homogeneity of PAN was affected by dissolution pathways in DMF and DMSO. In DMSO, PAN exhibited thermodynamic-controlled dissolution with better solubility. In DMF, PAN exhibited kinetic-controlled dissolution. Thermodynamic-controlled dissolution in DMSO resulted in better solution homogeneity.